2018
DOI: 10.1101/487850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The rice G protein γ subunit qPE9-1 positively regulates grain-filling process by interacting with abscisic acid and auxin

Abstract: 24The rice genome contains a single G α (RGA1) and G β (RGB1) and five G γ subunits. Recent 25 genetic studies have shown that DEP1/qPE9-1, an atypical putative G γ protein, is responsible 26 for dense and erect panicles, but the biochemical and molecular mechanisms underlying 27 control of grain size are not well understood. Here, we report that plants carrying qPE9-1 28 have more endosperm cells per grain than plants contain the qpe9-1 allele. The qPE9-1 line 29 has a higher rate and longer period of starch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(66 reference statements)
0
1
0
1
Order By: Relevance
“…HCP5 is an endogenous retrovirus that has become a component of the human genome (Teng et al, 2016). Liang et al (2018) suggested that HCP5 induces development of follicular thyroid carcinoma via acting as a miRNA sponge and could be useful for the diagnosis and therapy of FTC. Furthermore, there are nearly no relevant studies for other malignancies, previous reports concerning the relationship of HCP5 to BC are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…HCP5 is an endogenous retrovirus that has become a component of the human genome (Teng et al, 2016). Liang et al (2018) suggested that HCP5 induces development of follicular thyroid carcinoma via acting as a miRNA sponge and could be useful for the diagnosis and therapy of FTC. Furthermore, there are nearly no relevant studies for other malignancies, previous reports concerning the relationship of HCP5 to BC are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Могут быть взяты образцы с четырех стенок и углов полости матки. Учитывая тонкую структуру и гибкий материал устройства, его можно свободно вводить в полость матки и извлекать из нее, не требуя расширения шейки матки, что делает эту процедуру минимально инвазивной, безболезненной, безопасной и удобной [16].…”
Section: этиология и патогенез гиперплазии эндометрияunclassified